Development of eosinophilic inflammation is independent of B–T cell interaction in a chronic house dust mite‐driven asthma model. Issue 4 (22nd November 2016) - Vroman, H.; Bergen, I. M.; Li, B. W. S.; van Hulst, J. A. C.; Lukkes, M.; van Uden, D.; Hendriks, R. W.; Kool, M.
Summary: Background: Chronic exposure to environmental triggers, such as house dust mite (HDM), drives T helper 2 (Th2) cell‐mediated asthma. Recent evidence has shown that B–T cell interaction, and in particular germinal centre reactions and follicular T helper (Tfh) cells are required for the development of eosinophilic airway inflammation in HDM‐driven models containing a sensitization and challenge phase. Whether B–T cell interactions are essential for pulmonary eosinophilic inflammation following chronic allergen provocation remains unknown. Aims: In this study, we investigated the importance of B–T cell interaction in the development of eosinophilic airway inflammation and pulmonary remodelling in a chronic HDM‐driven asthma model. Methods: We exposed C57BL/6, Cd40l −/−, and Mb1 −/− mice to HDM three times a week for five consecutive weeks. Results: Chronic HDM exposure induced a pronounced eosinophilic allergic airway inflammation in broncho‐alveolar lavage fluid (BALf) and lung tissue, associated with the formation of immunologically active inducible bronchus‐associated lymphoid tissue (iBALT) in the lungs. The absence of B cells or lack of CD40L signalling did not hamper eosinophilic inflammation in the airways, although the number of Tfh and Th2 cells was substantially reduced in the lungs. Importantly, type 2 innate lymphoid cell (ILC2) numbers in BALf and lung were not affected by the absence of B cells or B–T cell interaction. Furthermore, eosinophilic airway inflammation is not sufficient to induce pulmonary remodelling and airway hyperresponsiveness. Conclusion and Clinical Relevance: From these findings, we conclude that B–T cell interaction is required for robust Tfh and Th2 cell induction, but not essential for eosinophilic airway inflammation during a chronic HDM‐driven asthma model.